Estimating shear wave velocity and site characterization of western Riyadh City, Saudi Arabia based on multichannel analysis of surface waves - Abdelrahman, Kamal; Saadon, Abdullah B.; Qaysi, Saleh (Frontiers in Earth Science, 2024)
The site characterization process is vital for the engineering structures and earthworks. In the current study, a Multi-Channel Analysis of Surface Waves (MASW) was carried out in western Riyadh City, Saudi Arabia. This aimed to determine subsurface geology, material stiffness, and potential weak zones approximately down to a depth of 30 m, and to propose the suitable seismic site characterization for precise foundation design. A total of 30 MASW lines were executed utilizing the Geode digital seismograph equipped with a 24-geophone array of 4.5 Hz. The data acquisition, processing, and inversion were meticulously calibrated to derive shear velocities representing subsurface geological conditions. The Vs30 map, based on estimated values ranging from 443.71 m/s to 639.78 m/s for soil, was prepared for the area. The results of the 1D and 2D Vs profiles tinted small Vs values at shallow depths. The resulting geological model is composed of sand, gravel, moderately weathered limestone, and hard limestone sequence. Analysis of shear wave velocities shows variations, indicating low shear velocity (representing sediments or rocks of low stiffness) juxtaposed with higher velocity layers (indicating rocks of higher stiffness) at depths greater than 10 m. This could imply the presence of a cavity or weak zone. The topmost shear wave velocity zone indicated materials with low Vs values (ranging from 180 m/s to 360 m/s), predominantly associated with stiff materials such as silty sand, gravel, and sandy deposits. The subsequent zone, with 3 to about 10 m depth, was characterized by medium to very dense soil with shear wave velocity values ranging from 360 m/s to 760 m/s, attributed to layers of silty clay and silty sand. At approximately 12 m, a high shear velocity layer (ranging from 760 m/s to 1,500 m/s) was identified, extending to a maximum depth of 22 m, potentially indicative of less weathered or fractured bedrock associated with limestone. While the deepest layer, with very high shear velocity (exceeding 1,500 m/s) beyond 22 m, indicated bedrock associated with hard limestone. The average Shear-wave velocity of soil for the whole study area (Vs30 = 551.2 m/s) suggests that the site can be classified as Class C (Very Dense Soil and Soft Rock) according to the National Earthquake Hazard Reeducation Program NEHRP (National earthquake hazards reduction program, 2001). These results will support, to a great extent, the design of engineering structures in the area of study.